ANALISIS PERHITUNGAN BIAYA PRODUKSI BERDASARKAN METODE FULL COSTING PADA NOSA ALUMINIUM - Surya Pratiwi, Cindy Afifah; Saraswati, Laila Isnaini; Fitriana, Noor Laila (UNIVERSITAS DHARMAWANGSA, 2024)
This research specifically aims to investigate and analyze the production cost calculation process applied in Nosa Aluminium's manufacturing operations using the full costing method. One of the main issues encountered in this study is that Nosa Aluminium has not adopted the appropriate method in setting the selling prices of its products. In collecting data, this research relies on primary qualitative data obtained through in-depth interviews and direct observation. The applied analysis method is descriptive analysis to describe and analyze the production cost calculation process. The results of this research affirm that the use of the full costing method provides greater accuracy in decision-making, especially in the context of setting selling prices of products.